A Cluster Study of Community-Based Tourism Terminology - SAY, Dietermar (Journal of Environmental Management and Tourism; Vol 12 No 8 (2021): JEMT, Volume XII, Issue 8(56), Winter 2021, 2021)
The lack of an official definition of “community-based tourism” (CBT) from the United Nations has caused the academics in the literature to debate the philosophy of the terminology. This paper collects and studies a list of CBT terminology changes in chronological order. Further observation reveals how the works in the CBT literature area have been mainly written by four groups of authors: 1) academics, 2) local government, NGOs, and 4) international organizations. A cluster of 90 CBT works are displayed through word cloud analysis presents evidence of the differences among these three different groups. The results show how the academics have a stronger focus on “community participation”, the government on “product placement”, and the international organizations on “development goals”. These results may allow future communities to more easily decide on which group of authors would suit them more when applying CBT practices.